PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. PASAR SWALAYAN MAJU BERSAMA GLUGUR - PETRUS LOO; KRISTINA . (JURNAL ILMIAH KOHESI, 2022)
The purpose of this study was to determine and analyze the effect of product quality, price and service quality on customersatisfaction at PT. Maju Bersama Supermarket Glugur. This research was conducted at PT. Maju Bersama SupermarketGlugur. The type of research used is descriptive quantitative research. The results showed that product quality, price andservice quality had a positive and significant effect both partially and simultaneously on customer satisfaction at PT. MajuBersama Supermarket Glugur. The R Square value of 83.70% indicates that the variable ability of product quality (X1), price(X2) and service quality (X3) has an effect on customer satisfaction (Y) at PT. Maju Bersama Supermarket Glugur while theremaining 16.30% is the influence of other independent variables that are not explained or researched by researchers in thisstudy such as promotion and location variables.